2008
DOI: 10.1016/j.virol.2007.10.009
|View full text |Cite
|
Sign up to set email alerts
|

An auto-regulatory loop for EBV LMP2A involves activation of Notch

Abstract: LMP2A is consistently detected in Hodgkin's lymphoma, nasopharyngeal carcinoma and has also been detected in Burkitt's lymphoma. Interestingly, LMP2A is detected in the absence of the transcriptional activator EBNA2, suggesting that an alternative mechanism is responsible for LMP2A expression. The intracellular domain of Notch (Notch-IC) and EBNA2 are functional homologs and recent microarray analysis indicates that LMP2A may constitutively activate the Notch pathway in vivo. Coupled with evidence that Notch-I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 67 publications
(102 reference statements)
1
20
0
Order By: Relevance
“…Gene expression profiling experiments have demonstrated that LMP2A interferes with the expression of numerous B-cell transcription factors, including EBF1 and E2A, and mimics many of the gene expression changes seen in HRS cells (Portis et al 2003;Portis and Longnecker 2004;Vockerodt et al 2013). LMP2A also activates the Notch pathway, and recent evidence suggests that these two factors may cooperate to further reinforce the loss of B-cell identity in HRS cells (Anderson and Longnecker 2008). Paradoxically, however, many of the adaptor molecules necessary for both BCR and LMP2A signalling are absent in HRS cells, and therefore, it remains unclear whether LMP2A acts as a BCR surrogate in HL.…”
Section: Contribution Of Ebv To the Pathogenesis Of Classical Hlmentioning
confidence: 99%
“…Gene expression profiling experiments have demonstrated that LMP2A interferes with the expression of numerous B-cell transcription factors, including EBF1 and E2A, and mimics many of the gene expression changes seen in HRS cells (Portis et al 2003;Portis and Longnecker 2004;Vockerodt et al 2013). LMP2A also activates the Notch pathway, and recent evidence suggests that these two factors may cooperate to further reinforce the loss of B-cell identity in HRS cells (Anderson and Longnecker 2008). Paradoxically, however, many of the adaptor molecules necessary for both BCR and LMP2A signalling are absent in HRS cells, and therefore, it remains unclear whether LMP2A acts as a BCR surrogate in HL.…”
Section: Contribution Of Ebv To the Pathogenesis Of Classical Hlmentioning
confidence: 99%
“…Consistent with a role in protection against apoptosis, LMP2a has been shown to provide B cells lacking a functional BCR with a survival signal in vivo (8) and to increase NF-B activation (16). LMP2a has also been shown to activate the Notch pathway (2). But LMP2a has not been shown, so far, to drive cell proliferation directly.…”
mentioning
confidence: 99%
“…Indeed, we have shown that LMP2A expression leads to the constitutive activation of Notch in B cells and epithelial cells. 12 Interestingly, the changes in transcriptional regulation seen in TgE-LMP2A mice are similar to those seen in an HRS cell in HL, linking LMP2A to the development of this malignancy. 10 Recently, aberrant activity of Notch1 has been linked to the down-regulation of E2A and EBF in HRS cells.…”
Section: Introductionmentioning
confidence: 66%
“…9,10 Notably, it appeared that LMP2A may constitutively activate the Notch pathway in vivo, a finding that has been confirmed in B cells and epithelial cells expressing LMP2A. 12 Because of the critical role that Notch signaling plays during B/T lineage specification, we sought to explore the possibility that LMP2A-mediated activation of Notch signaling in vivo may be responsible for the developmental changes seen in the B cells of TgE-LMP2A mice. By crossing our TgE-LMP2A mice with Notch1 lox/lox CD19 ϩ/Cre mice, we were able to demonstrate that LMP2A uses Notch1 signaling in vivo.…”
Section: Discussionmentioning
confidence: 99%